2015
DOI: 10.1002/ijc.29689
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to WCRF/AICR cancer prevention recommendations and metabolic syndrome in breast cancer patients

Abstract: Metabolic syndrome (MetS), conventionally defined by the presence of at least three out of five dismetabolic traits (abdominal obesity, hypertension, low plasma HDL-cholesterol and high plasma glucose and triglycerides), has been associated with both breast cancer (BC) incidence and prognosis. We investigated the association between the prevalence of MetS and a score of adherence to the World Cancer Research Fund (WCRF) and American Institute for Cancer Research (AICR) recommendations for the prevention of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…They reported a lower prevalence of metabolic syndrome with higher adherence to the recommendations. 8 Insulin resistance (assessed in the current study by the TG/HDL ratio) is one of the criteria for determining the metabolic syndrome. 45 Though the WCRF/AICR recommendations were issued for cancer prevention, studies have found that greater adherence to the recommendations is associated with lower risk of death from cancer-related 2 and other causes, 46, 47 which suggests that the recommendations may be relevant for cancer progression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They reported a lower prevalence of metabolic syndrome with higher adherence to the recommendations. 8 Insulin resistance (assessed in the current study by the TG/HDL ratio) is one of the criteria for determining the metabolic syndrome. 45 Though the WCRF/AICR recommendations were issued for cancer prevention, studies have found that greater adherence to the recommendations is associated with lower risk of death from cancer-related 2 and other causes, 46, 47 which suggests that the recommendations may be relevant for cancer progression.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, only two previous studies have examined associations between adherence to the cancer prevention recommendations and biomarkers of inflammation, oxidative stress and the metabolic syndrome, which could represent potential biological pathways mediating the association between adherence to the WCRF/AICR recommendations and cancer risk. 7,8 In a sample of 275 premenopausal women, adherence to the recommendations was associated with lower concentrations of biomarkers that indicate oxidative stress and inflammation, 7 while in a larger sample of 2,092 women diagnosed with invasive breast cancer, women who adhered to more dietary recommendations were less likely to develop metabolic syndrome, 8 a risk factor for breast cancer development and recurrence. 9,10 The development of some cancers is associated with states of chronic inflammation, hormonal response, hyperinsulinemia and insulin resistance.…”
mentioning
confidence: 99%
“…The study was approved by the Ethical Review Board of the National Cancer Institute of Milan (Italy). All participants belong to the intervention arm of the Diet and Androgen‐5 study (DIANA‐5) (Berrino et al., ; Bruno et al., ; Giallauria et al., , ; Villarini et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity improves body composition (Ligibel et al., ; Schmitz, Ahmed, Hannan, & Yee, ), cardiopulmonary and endothelial function (Berrino et al., ; Bruno et al., ; Giallauria et al., , ; Villarini et al., ), decreases serum levels of insulin over time, IGF‐I and increases IGF‐I‐binding proteins (Ballard‐Barbash et al., ; Ghose, Kundu, Toumeh, Hornbeck, & Mohamed, ; Giallauria et al., ; Irwin et al., ) that are likely to be important prognostic factors for BC (Pasanisi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is merely linked to metabolic dysregulations as insulin resistance, and associated with comorbidities as diabetes mellitus type 2, hypertension, cardiovascular complications and certain types of cancers [4]. Many reports has focused on the association of obesity with some types of cancers as adenocarcinoma of the esophagus, post-menopausal breast, ovarian, endometrium, liver, colorectal, gallbladder, pancreas, kidney, gastric cardia, as well as nonHodgkin lymphoma, multiple myeloma, metastatic prostate cancer, and unfortunately the list of cancer types is increasing [5][6][7][8][9][10][11]. Even more, obesity has been linked to increase the risk of recurrence, and deaths among cancer patients, thereby, better exploration and comprehensive understanding of the linking mechanisms between obesity and occurrence or aggressiveness of certain cancers, will allow the development of recent strategies against cancer [12][13][14].…”
Section: Introductionmentioning
confidence: 99%